Agronomic management controls microbial populations in soils of western Kenya - Kihara, Job Maguta; Bolo, Peter Omondi; Ayaga, George; Mukulama, John; Margenot, Andrew J.; Sommer, Rolf (International Center for Tropical Agriculture, 2018)
The provision of food requirements for current and future generations can be guaranteed through agricultural intensification options that safeguard the production resource base. Over the years, the debate on sustainable agricultural intensification has not been matched with due regard to how the intensification options influence the functions and balance of soil organisms and soil biology in general. Soil mesofauna and microorganisms have received very little attention so far. In sub-Saharan Africa (SSA) especially, there is very little knowledge and documentation of soil micro-organismal functioning and how these affect and are affected by the abiotic environment (soil physical and chemical properties, and climatic conditions), as well as agricultural management and intensification. Therefore, there is need to evaluate how measures to restore soil fertility and improve its productivity influence not only crop productivity and soil physical and chemical changes, but also soil biology, i.e. the diversity of macro-, meso- and micro-fauna and flora.